Effect of raw materials C/N ratio on the quality of Bokashi - Irfan; Dewi Yunita; Muhammad Fadhil; Fauzan (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: To assess the effect of C/N ratio in organic raw materials on the quality of bokashi and to obtain the proper C/N formulation of raw materials and fermentation time for bokashi production.